Entry into Force of the Law of the Sea Convention : with a Foreword by Sir Robert Y. Jennings - Moore, John Norton,; Nordquist, Myron H., (Center for Oceans Law and Policy ;, 1995)
The 1994 Rhodes Papers , beginning with a foreword by Sir Robert Y. Jennings, member and former President of the International Court of Justice, offer a collection of contributions dealing with the negotiations and events leading to the entry into force of the UN Convention on the Law of the Sea. The volume also includes contributions of key participants from the Third United Nations Conference on the Law of the Sea, the subsequent work of the Preparatory Commission, and the Secretary-General's consultations adjusting Part XI of the convention. The collection is based on presentations made during the annual seminar of the Center for Oceans Law and Policy (University of Virginia School of Law), held in May 1994, at Rhodes, Greece. Topics include: UN efforts to adjust Part XI and perspectives thereon; legal effects of entry into force for parties and nonparties; consideration of the Convention by the U.S. Senate; and current fisheries issues in relation to the Convention.